Growth Performance and Blood Profile of Broiler Chicken Fed Black Garlic and Curcuma in the Ration - Berliana Berliana; Nelwida Nelwida; Nurhayati Nurhayati (Buletin Peternakan, 2021)
This study aims to determine the effect of feeding black garlic and curcuma in the ration on the growth performance and blood profile of broiler chickens. This research was conducted in the Faculty Farm and Integrated Laboratory of the Faculty of Animal Science, Universitas Jambi and Health Laboratory, Jambi Province. The research used 200 day old chicken broiler (DOC) with strains of New Lohman MB 202. The experiment was carried out using a Completely Randomized Design (CRD) with 5 treatments and 4 replications, 10 chickens each. The treatments were: P0 = 100% commercial feed (control), P1 = P0 + 3.0% black garlic + 0% curcuma, P2 = P0 + 2.0% black garlic + 1.0% curcuma, P3 = P0 + 1.0% black garlic + 2.0 % curcuma  and P4 = P0 + 0% black garlic + 3.0% curcuma.  Parameters measured were bodyweight gain, feed consumption and conversion ratio, and blood cholesterol profile (total cholesterol, triglycerides, LDL and HDL). The data were analyzed according to the design used, and highly significant effect on parameter would be tested by Duncan's multiple range test. The results of this study showed that the treatment had a significant effect (P<0.05) on feed consumption, bodyweight gain, feed conversion ratio dan blood cholesterol properties. Duncan's test showed that feeding 2% of black garlic and 1% curcuma significantly (P<0.05) increased feed consumption as well as bodyweight gain and HDL whereas cholesterol, triglycerides and LDL decreased significantly (P<0.05). It is concluded that combination of 2% black garlic and 1% curcuma can improve growth performance up to 5% and blood profile of broilers (total cholesterol, Triglyceride and LDL decreased 8.62%, 36.59% and 28.43% respectively, HDL increased 9.15% approximately).